In silico identification of Tretinoin as a SARS-CoV-2 envelope (E) protein ion channel inhibitor. (December 2020) - Dey, Debajit; Borkotoky, Subhomoi; Banerjee, Manidipa
Abstract: Viroporins are oligomeric, pore forming, viral proteins that play critical roles in the life cycle of pathogenic viruses. Viroporins like HIV-1 Vpu, Alphavirus 6 K, Influenza M2, HCV p7, and Picornavirus 2B, form discrete aqueous passageways which mediate ion and small molecule transport in infected cells. The alterations in host membrane structures induced by viroporins is essential for key steps in the virus life cycle like entry, replication and egress. Any disruption in viroporin functionality severely compromises viral pathogenesis. The envelope (E) protein encoded by coronaviruses is a viroporin with ion channel activity and has been shown to be crucial for the assembly and pathophysiology of coronaviruses. We used a combination of virtual database screening, molecular docking, all-atom molecular dynamics simulation and MM-PBSA analysis to test four FDA approved drugs - Tretinoin, Mefenamic Acid, Ondansetron and Artemether - as potential inhibitors of ion channels formed by SARS-CoV-2 E protein. Interaction and binding energy analysis showed that electrostatic interactions and polar solvation energy were the major driving forces for binding of the drugs, with Tretinoin being the most promising inhibitor. Tretinoin bound within the lumen of the channel formed by E protein, which is lined by hydrophobic residues like Phe, Val and Ala, indicating its potential for blocking the channel and inhibiting the viroporin functionality of E. In control simulations, tretinoin demonstrated a lower binding energy with a known target as compared to SARS-CoV-2 E protein. This work thus highlights the possibility of exploring Tretinoin as a potential SARS-CoV-2 E protein ion channel blocker and virus assembly inhibitor, which could be an important therapeutic strategy in the treatment for coronaviruses. Highlights: Screened a database of 1806 small molecule compounds from DrugBank for potential SARS CoV-2 E protein inhibitors. Tested four FDA-approved drugs Tetinoin, Mefenamic acid, Ondansetron and Artemether as SARS CoV-2 E protein inhibitors . Used a combination of molecular docking, MD simulations and MM-PBSA analysis to propose Tretinoin as a promising inhibitor.